A family of genes encode the multiple forms of the Saccharomyces cerevisiae ribosomal proteins equivalent to the Escherichia coli L12 protein and a single form of the L10-equivalent ribosomal protein. - Newton, C H (1990)
The budding yeast Saccharomyces cerevisiae contains a family of genes that encodes four different but related small acidic ribosomal proteins designated L12eIA, L12eIB, L12eIIA, and L12eIIB and a single larger protein designated L10e. These proteins are equivalent (e) to the L12 and L10 proteins of Escherichia coli that assemble as a 4:1 complex onto the large ribosomal subunit. The five yeast genes (or their cDNAs) have been cloned and sequenced (M. Remacha, M. T. Saenz-Robles, M. D. Vilella, and J. P. G. Ballesta, J. Biol. Chem. 263:9044-9101, 1988; K. Mitsui and K. Tsurugi, Nucleic Acids Res. 16:3573, 3574, and 3575, 1988; this work). Here, the transcripts of these genes were characterized and quantitated and the proteins they encode were compared and aligned. Four of the genes, L12eIA, -IB, -IIA, and L10e, are uninterrupted, whereas the L12eIIB gene contains a 301-nucleotide-long intron between codons 38 and 39. The transcripts derived from each of these genes were analyzed by Northern (RNA) hybridization, primer extension, and S1 nuclease protection. All five genes are expressed, albeit at different levels. The transcript levels are coordinate and exhibit growth rate-dependent regulation in rich (glucose) and poor (ethanol) media. The five yeast proteins each contain a highly conserved acidic carboxy terminus of about 20 residues in length. This domain of unknown function is also present in archaebacterial but absent from eubacterial L10e and L12e proteins. Comparisons of the factor-binding domains in the yeast and other eucaryotic and archaebacterial L12e proteins indicate that the original duplication to produce the type I and II genes was a very ancient event. The evolutionary relationships between the eucaryotic, archaebacterial, and eubacterial L10e and L12e genes (and proteins) are discussed.